Ultra long-range interactions between silicon surfaces. (February 2016) - Na, S.R.; Sarceno, D.A.; Liechti, K.M.
Abstract: This paper takes a new look at interactions between hydroxylated silicon surfaces, which are commonly exploited in wafer bonding. In the past, strong connections have been made between the fracture toughness associated with such interactions. Here, we go one step further to examine the strength and range of the interactions, as well as the fracture energy from the perspective of traction-separation relations and cohesive zone modeling. The surface profiles of the interacting surfaces along with the initially bonded state were characterized by interferometry. The bonded silicon strips were separated by wedge loading while the separation of the surfaces was measured by infra-red crack opening interferometry. This data was used in conjunction with J-integral concepts to extract traction-separation relations directly. Variations in the fracture energy and strength and range of the interactions of a range of samples were linked to the mismatch in the waviness of the contact pairs and the amount of damage this caused. Finally, the strength and range of the interactions of well-bonded samples appeared to be linked to DLVO and capillary effects rather than van der Waals interactions.